"Sacrificial protection in action!": ultra-high stability of palladesite mineral towards the oxygen reduction reaction. Issue 3 (3rd January 2019) - Sarma, Saurav Ch.; Vemuri, Vamseedhara; Mishra, Vidyanshu; Peter, Sebastian C.
Abstract : Pd17 Se15 nanoparticles have been synthesized by a one-pot colloidal synthesis method. An accelerated degradation test confirms the ultra-high stability of the catalyst which gets enhanced after 50 000 cycles. Abstract : It is of the utmost importance to design an oxygen reduction electrocatalyst with high durability and good activity for large scale utilization in industry. Although several materials have been developed at the laboratory scale with extremely good activity, the durability of most of these materials is not sufficient enough to scale them up. Inspired by the high stability of naturally occurring minerals, we have synthesized palladesite (Pd17 Se15 ) via a one pot colloidal method. This material exhibits exceptionally high stability towards the oxygen reduction reaction (ORR) for at least 50 000 cycles, which is several times higher than that of many of the best reported materials. Due to the low surface energy of Se (0.10 J m −2 ) compared to that of Pd (1.43 J m −2 ), Pd active sites get protected by a Se overlayer. X-ray diffraction (XRD) and extended X-ray absorption fine structure (EXAFS) analyses confirmed that the material we have synthesized has the same crystal structure and atomic arrangement as the palladesite mineral. This nanomaterial holds great potential as the cathode material in PEMFCs in terms of facile one-pot synthesis, high conductivity without any support and enhanced ORR durability. DFT calculation reveals that the lower adsorption energy of the intermediate –OH and the enhancement of the adsorption energy of O2 and –OOH as Se gets oxidatively leached forming a Pd-enriched surface enhance its stability towards the ORR. The Se leaching has been experimentally confirmed by in situ XAFS and ICP analysis.